Thyroid hormone dysfunction in liver cirrhosis - Farooqui, Tajuddin; Shankar, B. Ravi; Rao, G. R. Srinivas; Donapati, Viswanath Reddy; Adi, Rakesh Kumar; Devalaraju, Madhavi (International Journal of Research in Medical Sciences, 2026)
Background: Chronic liver disease (CLD) relentlessly progresses to fibrosis and cirrhosis unless the causative agent is eliminated. Cirrhosis leads to hepatic dysfunction and additionally has an effect on several systems. Liver is vital to thyroid hormone metabolism and also in the synthesis of thyroid binding globulin. Low free T3 syndrome is described in liver cirrhosis. Aim was to investigate the thyroid function of patients with CLD in relation to the severity of the disease. Methods: This is a prospective observational, single centre, hospital-based case-control study, comparing thyroid function in 112 decompensated CLD subjects and 112 matched healthy controls. Results: In the present study majority of participants are between the ages of 31 to 50 years. TSH level was found to be elevated in hepatic encephalopathy (HE) patients with a higher West Haven grade compared to lower grades of encephalopathy. Reduced levels of FT3 and FT4 were found in higher grades of HE. MELD score and Child Pugh score severity correlation with FT3 has shown a reduced FT3 and was directly proportional to the severity of CLD. Conclusions: Patients with CLD showed abnormalities in thyroid hormone concentrations and these abnormalities were related to advanced Child Pugh score and MELD score. Serum T3 level has been found to be low in significant number of cirrhotic patients.